THE INFLUENCE OF DESTINATION IMAGE, SERVICE QUALITY, AND ELECTRONIC WORD OF MOUTH ON TOURIST SATISFACTION IN OLOMOUC CITY CENTER BASED ON INDONESIAN YOUTH - Runtuwarow, Imanuella Starry; Lapian, S. L. H. V.; Rumokoy, Lawren J. (Universitas Sam Ratulangi, 2024)
This study uses a quantitative with causal research approach. The data collected through questionnaire with convenience sampling technique that observed 103 respondents focussing on Indonesian youth who have visited Olomouc and analyzed using Multiple Linear Regression Analysis. The findings of this study demonstrate that destination image, service quality, and electronic word of mouth have a positive and significant impact on tourist satisfaction in Olomouc City Center among Indonesian youth, when considered simultaneously. However, when analyzed partially, only electronic word of mouth does not have a partial influence on tourist satisfaction. Keywords: Destination Image, Service Quality, Electronic Word of Mouth, Tourist Satisfaction